2020
DOI: 10.1101/2020.10.26.20219691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of the COVID-19 pandemic on eliminating trachoma as a public health problem

Abstract: Background: Progress towards elimination of trachoma as a public health problem has been substantial, but the COVID-19 pandemic has disrupted community-based control efforts. Methods: We use a susceptible-infected model to estimate the impact of delayed distribution of azithromycin treatment on the prevalence of active trachoma. Results: We identify three distinct scenarios for geographic districts depending on whether the basic reproduction number and the treatment-associated reproduction number are above … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The first two settings (Setting 1 and Setting 2) were intended to represent districts that would have been expected to reach the TF 1–9 <5% threshold before 2030 with a strategy of annual district-level MDA targeting the whole community, but where an interruption is expected to cause a delay in achieving this control threshold. This corresponds to ‘MDA subcritical’ as defined by Blumberg et al, 12 with R 0 >1 and R T <1.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…The first two settings (Setting 1 and Setting 2) were intended to represent districts that would have been expected to reach the TF 1–9 <5% threshold before 2030 with a strategy of annual district-level MDA targeting the whole community, but where an interruption is expected to cause a delay in achieving this control threshold. This corresponds to ‘MDA subcritical’ as defined by Blumberg et al, 12 with R 0 >1 and R T <1.…”
Section: Methodsmentioning
confidence: 97%
“… 10 , 11 In the context of programmatic activities being temporarily halted due to COVID-19, this is especially concerning for districts with previously high prevalence of trachoma that are midway through elimination programmes. Furthermore, for a limited number of districts, the reproductive number under annual treatment ( R T ) has been estimated as being >1 (defined as ‘MDA super-critical’ by Blumberg et al), 12 suggesting that for this minority of districts, elimination is not achievable under a strategy of annual MDA. 12 , 13 For such districts there is concern that the interruption to programmes may cause a particularly marked surge in transmission with unknown consequences for morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 In such settings, the current modelling suggests biannual or quarterly MDA could help catch up on missed MDA rounds and help accelerate progress towards the 2030 trachoma goals. 5 The benefits of more frequent MDA have been demonstrated with a randomized trial that found quarterly MDA targeted at children was more effective in reducing Chlamydia trachomatis infection compared with community-wide annual MDA. 6 While benefits of more frequent MDA need to be balanced against cost and logistical considerations, shorter programmes are likely to yield cost savings in the long-term, as well as reduce the total amount of antibiotics required and the likelihood of antimicrobial resistance emerging.…”
mentioning
confidence: 99%